2004
DOI: 10.1101/lm.70904
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Modulation of Visual Attention and Working Memory: Dissociable Effects of Basal Forebrain 192-IgG-saporin Lesions and Intraprefrontal Infusions of Scopolamine

Abstract: Two experiments examined the effects of reductions in cortical cholinergic function on performance of a novel task that allowed for the simultaneous assessment of attention to a visual stimulus and memory for that stimulus over a variable delay within the same test session. In the first experiment, infusions of the muscarinic receptor antagonist scopolamine into the medial prefrontal cortex (mPFC) produced many omissions but did not impair rats' ability to correctly detect a brief visual stimulus. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 75 publications
6
97
0
Order By: Relevance
“…Similarly, Chudasama et al (2004) found no effect on response accuracy when cue duration was reduced from 1 s to 250 ms (although they did see a threefold increase, relative to controls, in the number of trials on which lesioned rats failed to respond, which might also indicate impairment in detecting or attending to those cues). Thus, the role of SI/ nBM itself in this task is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chudasama et al (2004) found no effect on response accuracy when cue duration was reduced from 1 s to 250 ms (although they did see a threefold increase, relative to controls, in the number of trials on which lesioned rats failed to respond, which might also indicate impairment in detecting or attending to those cues). Thus, the role of SI/ nBM itself in this task is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-trial interval was 5 s, and the task ended after 125 trials were completed or 60 min passed, whichever came first. The task utilized here is operationally similar to a recent task described by Chudasama and Robbins (Chudasama et al, 2004;Chudasama and Robbins, 2004a), with the exception that their task uses shorter stimulus durations (to tax attentional processes) and involves a match contingency.…”
Section: Delayed Nonmatch-to-sample Trainingmentioning
confidence: 99%
“…Second, rats given selective cholinergic lesions in the NBM were not found to exhibit clear deficits in water-maze (Galani et al, 2002) and radial-maze tasks (Galani et al, 2002;Lehmann et al, 2003). Third, Chudasama et al (2004) showed that following injections of 192 IgG-saporin into the NBM, trained rats performed normally under conditions of low-and even high-attentional demands in a combined attention-memory task, but were impaired when tested for memory of the stimulus location. Previously, Risbrough et al (2002) reported similar conclusions on attention after submaximal cholinergic lesions in the NBM.…”
Section: Igg-saporin Lesions: Memory Vs Attentionmentioning
confidence: 99%